Gestão do conhecimento: visão de indivíduos e organizações no Brasil - Cianconi, Regina de Barros (2003)
This thesis discusses Knowledge Management, its concept and application, base don literature analysis and field research. The main hypothesis of this thesis was that Knowledge Management through its new technologies and networking would contribute to the change of working methods and information retrieval and use. It was also considered that its methodologies and tools would result in potential increase of productivity, better interaction among professionals, as well as on personal, professional and organizational growth. But, in spite of these benefits, many companies in Brasil do not implement Knowledge Management in its broad capabilities, which would imply in an increase of motivation for information sharing and in changes in the relationship among companies and employees and also of practices that enable collaboration and reuse of tacit and explicit knowledge, through human capital (companies personnel), organizational capital, this one including technologies know-how, methodologies and processes, and social capital resulting from as corporative knowledge, Knowledge Management must consider both on its methodologies and practices. However, due to cultural and social barriers, including practices of information gathering and use, this is not what is seen in several cases. In order to certigy this work hypothesis, Knowledge Management s aims and practices were analyzed in relation to tacit and explicit knowledge, through the results of the field research carried out. The first part of the research consisted of bibliographic review and the insertion of Knowledge Management approach on social and organizational theory and practices